Construction sector: Full order books, good growth prospects - Martin Gornig; Claus Michelsen (DIW Economic Bulletin, 2017)
A significant rise in Germany's construction volume is expected for this year and the next, even if the growth is not as pronounced as it was in 2016. According to DIW Berlin's latest construction volume calculations, the sum of all new construction and building refurbishments will increase in real terms by 1.6 and 2.4 percent in 2017 and 2018, respectively, from a rate of 2.5 percent in 2016. New housing construction and public civil engineering are currently the primary growth drivers, but refurbishments are also likely to gain in prevalence. Yet it is also becoming apparent that the construction industry is reaching the limits of its production capacities, with high utilization levels in many places. Government subsidization of construction investment is thus inappropriate in this context: given the full construction capacities, measures intended to promote new construction will only catalyze the price acceleration. The focus should instead be on approaches to stabilizing investment, which can be achieved through instruments for urban redevelopment or the creation of a reserve in public budgets for infrastructure investment.
Keywords: E32; E66; 330; construction industry; residential construction; public infrastructure; economic outllok